Assessing the Validity of Claims-Based Diagnostic Codes for Psychotic and Affective Disorders and the Influence of the Coding Transition from the ICD-9 to the ICD-10 in Taiwan’s National Health Insurance Research Database - Wang YW; Liu CC; Chen HC; Wu CS; Chan JH; Chen CC; Huang WL; Liao SC; Hwang T; Chen WJ (Clinical Epidemiology)
Yen-Wen Wang,1 Chen-Chung Liu,2 Hsi-Chung Chen,2 Chi-Shin Wu,3,4 Jen-Hui Chan,5 Cheng-Che Chen,6 Wei-Lieh Huang,4 Shih-Cheng Liao,2,5 Tzung–Jeng Hwang,2 Wei J Chen1,2,7,8 1Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, Taiwan; 2Department of Psychiatry, College of Medicine and National Taiwan University Hospital, National Taiwan University, Taipei, Taiwan; 3National Center for Geriatrics and Welfare Research, National Health Research Institutes, Miaoli, Taiwan; 4Department of Psychiatry, National Taiwan University Hospital Yunlin Branch, Yunlin, Taiwan; 5NTU Hsin-Chu Hospital, National Taiwan University Hsin-Chu Branch, Hsinchu, Taiwan; 6NTU Biomedical Park Hospital, National Taiwan University Hsin-Chu Branch, Hsinchu, Taiwan; 7Department of Public Health, College of Public Health, National Taiwan University, Taipei, Taiwan; 8Center for Neuropsychiatric Research, National Health Research Institutes, Miaoli, TaiwanCorrespondence: Wei J Chen, Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, Taiwan, Email wjchen@ntu.edu.twPurpose: No studies have validated psychiatric diseases diagnoses in Taiwan’s National Health Insurance Research Database (NHIRD). We aimed to assess the interrater reliability of chart-review among psychiatrists, examine the validity of the diagnostic codes for psychotic disorders and affective diseases in the NHIRD against review-based diagnoses, and examine whether the change in the coding system from the ICD-9-CM to the ICD-10-CM affected the validity of the diagnostic codes.Patients and Methods: The study participants were psychiatric inpatients aged 18 to 65 years who were admitted in 2015 and 2017, respectively, to the main and three branch hospitals of National Taiwan University Hospital. A chart review was conducted among 48 purposively selected inpatients with discharge diagnoses in five core categories to assess interrater reliability. This chart-review procedure was then used to generate diagnostic codes for a stratified sampling of 727 inpatients with discharge diagnoses in 12 diagnostic categories of psychotic disorders and affective disorders to examine the validity of the diagnostic codes.Results: The intraclass correlation coefficient reliability of schizophrenia and three broad categories of diagnoses indicated good interrater reliability. The positive predictive value and sensitivity of common diagnoses in the narrow category (eg, schizophrenia) or the broad category (eg, psychotic disorders, bipolar disorders, and major depressive disorders) were high-performing (≥ 0.70), whereas those of the diagnoses of low prevalence were modest. The validity indices of claims-based diagnoses using the ICD-10-CM tended to be better than those using the ICD-9-CM.Conclusion: This first-ever study validating psychiatric diagnoses in Taiwan’s NHIRD using a structured chart review suggests that the diagnostic codes of narrow categories of schizophrenia or other broad categories are recommended for high-performing validity indices. Intensive training for the coding plus the specific details requested by the ICD-10 may increase the validity of the claims-based databases for psychotic and affective disorders.Plain Language Summary: Mental disorders such as psychotic disorders and affective disorders have contributed substantially to the global burden of disease. Since Taiwan launched the National Health Insurance (NHI) in 1995, its claims data have been compiled into the National Health Insurance Research Database (NHIRD), which has a coverage rate over 99% of Taiwan’s population and is thus widely used by researchers. However, the validity of the diagnostic codes for psychotic disorders and affective disorders and the impact of the coding system transition in the NHIRD have not been examined. In this study, we developed a standardized process for reviewing the medical records of psychiatric inpatients at one medical center and its branches in suburban or rural areas, which provided an opportunity to examine the validity of psychiatric diagnoses in hospitals across urbanicity levels in the NHIRD. Among 48 inpatients in five core categories, including schizophrenia, manic/mixed episode with psychotic features, depressive episode with psychotic features, bipolar disorder without psychotic features, and major depressive disorder without psychotic features, good interrater reliability was achieved. In another 727 inpatients with psychotic and affective disorders, the positive predictive value and sensitivity of common diagnoses in the narrow category (eg, SZ) or broad category (eg, psychotic disorders, bipolar disorders, and major depressive disorders) were high-performing (≥ 0.70), whereas those of the diagnoses of low prevalence were modest. Intriguingly, the validity indices of claims-based diagnoses using the International Classification of Diseases, Tenth Revision (ICD-10) tended to be better than those using the ICD-9.Keywords: psychiatry, psychotic disorders, health insurance database, positive predictive value, sensitivity, interrater reliability, intraclass correlation coefficient reliability, electronic health records